2007
DOI: 10.3346/jkms.2007.22.5.932
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Placenta Increta Presenting as Delayed Postabortal Intraperitoneal Bleeding in the First Trimester

Abstract: Placenta increta is an uncommon and life-threatening complication of pregnancy characterized by complete or partial absence of the decidua basalis. Placenta increta usually presents with vaginal bleeding during difficult placental removal in the third-trimester. Although placenta increta may complicate first and early second-trimester pregnancy loss, the diagnosis can be very difficult during early pregnancy and thus the lesion is difficult to identify. We encountered with a woman who was diagnosed with placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 11 publications
(12 reference statements)
0
11
0
12
Order By: Relevance
“…Unlike this, in our case it presented as intermittent bleeding following a second trimester abortion. A case of placenta increta diagnosed after emergency hysterectomy done in view of intraperitoneal bleeding two months after an uncomplicated dilatation and curettage for first trimester abortion was also reported [4]. Also, Choi et al reported uterine rupture in normal intrauterine pregnancy at 13 weeks of gestation due to placenta percreta [5].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike this, in our case it presented as intermittent bleeding following a second trimester abortion. A case of placenta increta diagnosed after emergency hysterectomy done in view of intraperitoneal bleeding two months after an uncomplicated dilatation and curettage for first trimester abortion was also reported [4]. Also, Choi et al reported uterine rupture in normal intrauterine pregnancy at 13 weeks of gestation due to placenta percreta [5].…”
Section: Discussionmentioning
confidence: 99%
“…Néanmoins, Esmans et al ont rapporté le cas d'un placenta percreta responsable d'une rupture utérine à la fin du premier trimestre de la grossesse sur un utérus sain [18]. Pour tous ces cas, le diagnostic a été fait rétrospectivement, à la suite d'hémorragies spontanées ou provoquées, nécessitant dans la plupart des cas une hystérectomie [19][20][21]. L'examen de la pièce opératoire a mis en évidence des agrégats multifocaux de trophoblaste ainsi que des villosités choriales pénétrant le myomètre et pouvant atteindre la séreuse utérine [20].…”
Section: Discussionunclassified
“…Pour tous ces cas, le diagnostic a été fait rétrospectivement, à la suite d'hémorragies spontanées ou provoquées, nécessitant dans la plupart des cas une hystérectomie [19][20][21]. L'examen de la pièce opératoire a mis en évidence des agrégats multifocaux de trophoblaste ainsi que des villosités choriales pénétrant le myomètre et pouvant atteindre la séreuse utérine [20]. Lorsque l'attitude conservatrice, avec embolisation des artères utérines, a été possible et efficace, l'examen anatomopathologique du produit d'aspiration concluait à des caillots et du tissus villositaire dégénératif [22].…”
Section: Discussionunclassified
“…Son et al reported a patient who presented with intra peritoneal bleeding 2 months after an uncomplicated uterine curettage in the first trimester. The patient underwent an emergency hysterectomy, which confirmed placenta increta post-operatively (14). Liao et al described the use of laparoscopic assisted vaginal hysterectomy for their patient with placenta accrete at 9 weeks gestation although it was complicated with bladder injury intra-operatively (12).…”
Section: Figurementioning
confidence: 99%